Impact of lifetime variations and secondary barriers on CdTe solar-cell performance - Pan, Jun, author; Sites, James R., advisor; Patton, Carl, committee member; Gelfand, Marty, committee member; Menoni, Carmen, committee member (Colorado State University. Libraries, 2007)
The thin-film CdTe solar cell (generally n-CdS/p-CdTe) is one of the leading candidates for terrestrial photovoltaic applications due to its low cost and high efficiency. However, compared with single-crystal cells of comparable band gap, there remains a significant voltage difference, where the best CdTe cells are about 250 mV below the best GaAs cells when an appropriate adjustment is made for bandgap. Therefore, the fabrication of high-voltage CdTe solar cells is one of the major and critical challenges in recent years. From a device-physics point of view, variations in carrier lifetime, carrier (hole) density, and other aspects such as a back electron reflector, should be able to improve the voltage and efficiency. This dissertation systematically studies the impact of lifetime variations and secondary barriers on CdTe solar-cell performance. Numerical simulation is used to evaluate how combinations of lifetime, carrier density, interfacial recombination, and back barriers affect cell behaviors. Strategies to improve voltage and cell performance are explored. The experimentally observed characteristics with significant back contact barrier (back-hole barrier) are explained. Current-voltage distortion which would result from a front barrier is also discussed. In the absence of secondary barriers, higher voltage and fill factor should be obtained, but only by a moderate amount, when the carrier lifetimes are increased from today's typical value (0.5 ns). Similarly, increased hole density (above the typical 2 x 1014 cm-3) should lead to higher voltage, but with today's lifetimes, low collection outside the depletion region will lead to a drop in the current. Hence, both higher lifetime and higher carrier density are needed to obtain significantly higher voltage. The effect of lifetimes with secondary back barriers is also explored. The combination of a significant back-hole barrier and a typical CdTe carrier density leads to two competing mechanisms that can alter the J-V characteristics in two different ways depending on the lifetime. One is a hole limitation on current in forward bias, which reduces fill-factor and efficiency. The second is a high electron contribution to the forward diode current, which results in a reduced voltage. CdTe solar cells are particularly prone to the latter, since the combination of a wide depletion region and impedance of light-generated holes at the back contact increases electron injection at the front diode. Simulated J-V curves illustrating the two major effects are in good agreement with experimental curves that have been observed in recent years. When an effective electron reflector is present at the back contact, the voltage should be increased because of the reduced voltage-limiting back recombination, and the lifetimes for high efficiency need not to be particularly high. A fully depleted CdTe layer (hole density of 2 x 1013 cm-3) with such a back-electron reflector and moderate lifetime should significantly increase voltage. The electron reflector could of course be applied to CdTe that is not fully depleted. In this case, the benefit is relatively small when the lifetime is moderate, because the carrier densities at the back would not be large enough for back recombination to significantly lower the voltage. A secondary front barrier in CdS/CdTe solar cell may block the electron current at both directions in the front. There are several possible causes for such a front barrier: high conduction-band offset (CBO) between TCO and CdS, highly photoconductive CdS layer, or a dipole CdS on the p-type CdTe layer. Numerical simulations show that high front barrier caused by dipole CdS may result in fill-factor and efficiency losses, thus J-V distortion. The maximum energy difference between the conduction band and the quasi-Fermi level for electrons in the front is the key parameter.
Keywords: condensation; energy; condensed matter physics